Low frequency of N-methyl-D-aspartate receptor autoimmunity in tick-borne encephalitis - Jakob Morén; Barbro Persson; Anna Sörman; Åke Lundkvist; Hanin Shihab; Marie Studahl; Malin Veje; Göran Günther; Gabriel Westman (PLoS ONE, 2025)
Background Tick-borne encephalitis is a viral infection of the central nervous system that may cause severe illness and long-term sequelae, to which underlying mechanisms are not completely understood. Autoantibodies against the N-methyl-D-aspartate receptor (anti-NMDAR) may be triggered by immunologic events, occur sporadically, and can cause autoimmune encephalitis. Following herpes simplex encephalitis and Japanese encephalitis, anti-NMDAR autoantibodies may develop and have been associated with relapse or impaired cognitive recovery. Tick-borne encephalitis has been shown to trigger anti-NMDAR encephalitis in sporadic cases, but the frequency of autoimmunization is unknown. Objectives The objective of this study was to assess the frequency of intrathecal anti-NMDAR antibody development following tick-borne encephalitis and to explore whether such antibodies could be relevant to cognitive complaints. Methods Adult patients with tick-borne encephalitis were included retrospectively from one cohort and prospectively from another. A stored post-acute cerebrospinal fluid sample was required for anti-NMDAR analysis. Two commercial kits (Euroimmun AG, Lübeck, Germany) were used to detect anti-NMDAR IgG antibodies in cerebrospinal fluid. Results A total of 71 cerebrospinal fluid samples from 53 patients were analyzed for anti-NMDAR antibodies. Samples were obtained at a median of 91 days (range 21–471) after onset of central nervous system symptoms. Anti-NMDAR antibodies were detected in two samples from a single tick-borne encephalitis patient, corresponding to 1.9% of patients (95% CI: 0.05–10.1%). Conclusions The development of intrathecal anti-NMDAR autoantibodies following tick-borne encephalitis is a rare event, and further studies are needed to clarify their potential relevance to cognitive outcomes in a minority of cases. Testing for anti-NMDAR antibodies in cerebrospinal fluid may be considered in patients who experience clinical deterioration following an initial recovery.